(untitled) (Scientific journal of the Fergana State University, 2023)
This article provides information on the chemical composition, biologic activity and antioxidant activity of food additives "Asdavo". In contrast to the methods used by the above scientists by us, the antioxidant activity of alcohol and aqueous extracts of the food additive "Asdavo" was studied using Cary 60 UV-Vis Agilet Technologies spectrophotometerometri in the method of spectrophotometric analysis.